Answers

The Brainliest Answer!
2015-08-26T16:08:28+05:30
⇒ (x-1)³ = 2³
applying cube roots on both sides
⇒ ∛(x-1)³ = ∛2³
⇒ x-1=2
⇒ x=2+1
⇒ x=3

(x+1)² =?
put x=3 as we solved it above
so,
    =(3+1)²
    = 4²
    = 16.
therefore,
(x+1)² =16

4 4 4
she explained it well
but sometimes if we use direct steps some users may not know how do we get that... So we have to provide our best to the users although it is simple or tough
(Y) ur ryt :p :)
:) thnk uu
wlcme
2015-08-26T16:10:36+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(x-1) = ∛8
x-1 = 2
x= 2+1
x=3
So, (x+1)² = (3+1)²
(4)² = 16

2 3 2